Recent advancements in legumes: Next generation sequencing and omics approaches - UDAWAT, PUSHPIKA (The Indian Journal of Agricultural Sciences, 2023)
Legumes are important food crops in sustaining food security globally along with improving physio-chemical soil properties by mechanism of biological nitrogen (N2) fixation. Different types of abiotic stresses (especially their intensity, duration, and magnitude) such as drought, salt, cold and heat affect crop yield negatively and threaten overall food security. As the world population is expanding rapidly on the limited agricultural resources, sustainable management of the same is the need of the hour. Legumes are major nitrogen fixers that are enriched with metabolites, which provide second line of defence against several biotic as well as abiotic stresses. In past years genome sequence information of several grain legumes has been well documented. Due to genome sequencing, re-sequencing and RNA sequencing (RNA Seq.) of grain legumes, information associated to legume development, structural variation, differentially expressed genes and functional genomics was made available. Regulation of entire plant physiology and nitrogen fixation in grain legumes during abiotic stress is multifaceted and only some pathways have been revealed. This review is focussed on exploring the genetic variations analysed through omics approaches to enhance crop yield and productivity under drought, salt, cold and heat stress of grain legumes. Therefore this reviewis a compilation of recent biotechnological advancements on grain legumes using omics approaches for better understanding of their abiotic stress tolerance.